Hidden in Plain Sight: Conceptualizing Platform Auxiliaries and Their Conflicting Impacts on Platforms' Value Architecture - Cutolo, Donato; Hargadon, Andrew; Kenney, Martin (Wiley, 2026)
This paper introduces the concept of platform auxiliaries to identify a set of actors that provide independent resources explicitly designed to support complementors in their value creation and capture activities. Platform auxiliaries capitalize on unmet needs of complementors within platforms, offering services such as third-party software development kits (SDKs) for app developers, social media analytics tools for content creators, rental management software for hosts, and even fake review services for sellers. Although the presence and relevance of these actors have been largely overlooked in platform research, we demonstrate the importance of recognizing their distinctive role and their conflicting impacts on platform value architectures. Specifically, we theorize three mechanisms through which auxiliaries support complementors (augmenting their development and commercialization capabilities on the focal platform, increasing access to platform-specific information, and expanding their activities beyond the focal platform), discussing how they enhance complementors' engagement and innovation potential, thereby fostering generativity on the platform. Yet, because auxiliaries operate outside the architectural framework established by the platform owner, in supporting complementors, they may reshape fundamental channels underpinning architectural stability, such as platform curation, information distribution, and platform compatibility, potentially weakening the control mechanisms through which the platform owner manages the platform and captures value.
Keywords: 62 Ciencias de las Artes y las Letras::6201 Arquitectura; ODS 9 - Industria, innovación e infraestructura; complementors; platform architecture; platform auxiliaries; platform ecosystems; platform entrepreneurship; platform governance; platforms